2011
DOI: 10.1089/neu.2011.1921
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride Improves Locomotor Recovery after Spinal Cord Injury

Abstract: Amiloride is a drug approved by the United States Food and Drug Administration, which has shown neuroprotective effects in different neuropathological conditions, including brain injury or brain ischemia, but has not been tested in spinal cord injury (SCI). We tested amiloride's therapeutic potential in a clinically relevant rat model of contusion SCI inflicted at the thoracic segment T10. Rats receiving daily administration of amiloride from 24 h to 35 days after SCI exhibited a significant improvement in hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…TMX effects on oligodendrocyte/myelin levels can explain the improvement in BBB scores. We have shown that loss of myelin levels at the lesion site in chronically injured spinal cords is correlated with BBB scores, 56 in agreement with other findings. 57 Further, we have also demonstrated that even modest increases in myelin (i.e., MOG) levels by *12% at the lesion site lead to substantial improvements of locomotor recovery.…”
Section: Translational Potential Of Tamoxifensupporting
confidence: 93%
See 1 more Smart Citation
“…TMX effects on oligodendrocyte/myelin levels can explain the improvement in BBB scores. We have shown that loss of myelin levels at the lesion site in chronically injured spinal cords is correlated with BBB scores, 56 in agreement with other findings. 57 Further, we have also demonstrated that even modest increases in myelin (i.e., MOG) levels by *12% at the lesion site lead to substantial improvements of locomotor recovery.…”
Section: Translational Potential Of Tamoxifensupporting
confidence: 93%
“…57 Further, we have also demonstrated that even modest increases in myelin (i.e., MOG) levels by *12% at the lesion site lead to substantial improvements of locomotor recovery. 56 Therefore, our finding that TMX increases levels of all major myelin proteins (MBP, CNPase, MOG), and oligodendrocyte numbers by *20% at T10 can explain the observed improvement in hind-limb motor recovery (by *3 BBB scores).…”
Section: Translational Potential Of Tamoxifenmentioning
confidence: 72%
“…Based on the above results, we here used amiloride, a therapeutic agent that has been shown to have cytoprotective and ER stress‐modulating effects in various models of neurological diseases, including SCI (Friese et al ., ; Arias et al ., ; Durham‐Lee et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Among the few studies that investigated the effects of amiloride in an SCI model, one report showed that amiloride had neuroprotective effects in an in vitro model of SCI (Agrawal & Fehlings, ). Another study reported improvements in hindlimb function and increased myelin oligodendrocyte glycoprotein in a rat SCI model (Durham‐Lee et al ., ). Similarly, in our current study, significant improvements in hindlimb function were observed after amiloride administration in a rat SCI model, possibly brought about by the reduced cell death revealed by TUNEL assays.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation